EFEK MEDIATOR VASCULAR CELL ADHESION MOLECULE-1 (VCAM-1) TERHADAP SEVERITAS DAN OUTCOME PASIEN STROKE ISKEMIK AKUT - Assa, Christantina Pradescha; Bahar, Ashari; Akbar, Muhammad; Bintang, Andi Kurnia; Tammasse, Jumraini; Soraya, Gita Vita; Halim, Wijoyo (Molucca Medica, 2024)
Introduction: Atherosclerosis is currently recognized as part of the inflammatory disease. In the acute phase, inflammation causes brain edema and expansion of ischaemic area. Vascular cell adhesion molecule 1 (VCAM-1) plays a crucial role in the inflammation mechanism immediately after cerebral damage in stroke, facilitating the migration of leukocytes across the endhothelial cells. Objective: This study aimed to establish the correlation between VCAM-1 serum levels and severity and outcomes in stroke patients. Research Methodology: It was a cross-sectional study conducted from September to November 2023 on 51 patients with acute ischemic stroke at RSUP Wahidin Sudirohusodo Makassar and other affiliated hospitals. VCAM-1 serum levels were examined using the ELISA principle. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) upon admission, and clinical outcomes were evaluated using the modified Rankin Scale (mRS) on the 30th day of onset. Results: Mann- Whitney test results showed no difference in serum VCAM-1 levels between severity groups (mild and moderate) and clinical outcome groups (good and poor). Spearman correlation test results indicated a correlation between serum VCAM-1 levels and severity (p=0.635, r=-0.068) and clinical outcomes (p=0.459, r=-0.106). Conclusion: There is no association between serum VCAM-1 levels and the severity and clinical outcomes of acute ischemic stroke patients. Recommendation: Further research is needed to explore the relationship between serum VCAM-1 levels and severity and clinical outcomes in acute ischemic stroke patients at various centers in Indonesia.